Barriers to utilization of focused Antenatal care services among pregnant women in Basrah governorate - Jinan, ALRamdhan; Maisaa, ALABRAHIM; Azha, Al-Hilfi; Huda, Al-Abboodi (Scientific Journal of Medical Research, 2024)
Introduction: Along with family planning, skilled delivery services, and emergency obstetric care, focused antenatal care (FANC) is a crucial component of a package of initiatives aimed at improving maternal and newborn well-being. Objective: The present study was conducted to identify demographic, as well as social and cultural factors that may contribute to low utilization of FANC services in Basrah among pregnant and post-natal women. Methodology: This research is a cross-sectional study to find out obstacles to the use of centered prenatal care services among pregnant women in the governorate of Basrah. Result: About 116 (34.6%) were in the age group 21 to 25 years. The majority 147 (43.9%) of women had finished primary or intermediate school. Most of the women under study, 318 (94.9 %) were not employed. A high percentage of husbands (49%) had finished primary or intermediate school and (39.7%) of husbands had been government employees. 28.0% of the women under study had only one baby, and most of the study population, 290 (86.3%), had accepted socioeconomic status. Conclusion: The study identified a statistical significance between low utilization and parity, being too busy, living away from antenatal care services and cost of transportation, long waiting time, and also identified a statistical significance between knowledge, attitude of the participants and low utilization of focused antenatal care.